2022
DOI: 10.3390/catal12030272
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/ZnS-Polyvinyl Alcohol Hydrogel for Photocatalytic H2-Generation

Abstract: The separation of nanoparticles from a solution-based photocatalytic reaction is a significant problem in practical applications. To address the issue, we developed a new photocatalyst composite based on ZnO-ZnS heterojunction (ZnOS) embedded in polyvinyl alcohol (PVA) hydrogel, which showed satisfactory results for photocatalyst recycling. PVA-ZnOS composite hydrogel was fabricated by freezing-induced gelation, which enabled the encapsulation of ZnOS nanoparticles into polymeric matrices. PVA hydrogel served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For these reasons, PVA-based composite hydrogels have shown good performance in the photocatalytic generation of H 2 and good recyclability. [46] Jiang et al underlined that the hydrogel structure (HR) can inhibit the CdS and ZnS quantum dots agglomeration phenomena and because of synergistic effects between quantum dots and hydrogel structure, the hydrogel-photocatalyst composites (CdS/HR and ZnS/HR) showed high H 2 evolution rates (~8 mmol g À 1 ) compared to the H 2 production observed with unsupported CdS and ZnS nanoparticles (sacrificial agent: Na 2 SÀ Na 2 SO 3 ). [30b] Sai et al have synthesized functional hybrid polyelectrolyte hydrogels containing self-chromophore amphiphiles, [47] evidencing a hydrogen production rate of 107.4 mol mol cat À 1 h À 1 (sacrificial agent: ascorbic acid) [47] .…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, PVA-based composite hydrogels have shown good performance in the photocatalytic generation of H 2 and good recyclability. [46] Jiang et al underlined that the hydrogel structure (HR) can inhibit the CdS and ZnS quantum dots agglomeration phenomena and because of synergistic effects between quantum dots and hydrogel structure, the hydrogel-photocatalyst composites (CdS/HR and ZnS/HR) showed high H 2 evolution rates (~8 mmol g À 1 ) compared to the H 2 production observed with unsupported CdS and ZnS nanoparticles (sacrificial agent: Na 2 SÀ Na 2 SO 3 ). [30b] Sai et al have synthesized functional hybrid polyelectrolyte hydrogels containing self-chromophore amphiphiles, [47] evidencing a hydrogen production rate of 107.4 mol mol cat À 1 h À 1 (sacrificial agent: ascorbic acid) [47] .…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…Hydrogel‐based photocatalyst composed of ZnO/ZnS nanoparticles embedded into the polyvinyl alcohol (PVA) polymeric matrix was prepared by Poliukhova et al [46] . The observed H 2 production rate under UV light was 18.8 μmol ⋅ h −1 from a 0.1 M Na 2 S and 0.1 M Na 2 SO 3 aqueous solution.…”
Section: Hydrophilic Polymer‐photocatalyst Compositesmentioning
confidence: 99%
“…29,30 Additionally, some PVA macromolecular chains produce agglomerates, forming insoluble or even insoluble granular structures that hinder internal crosslinking configurations and affect the mechanical properties of hydrogels. 27,31,32 Polyethylene glycol (PEG) is a non-toxic and harmless polymer with small steric hindrance and active group hydroxyl (-OH) 33,34 at both ends. The introduction of PEG can better link the macromolecular chains of PVA, minimize the cross-linking error, facilitate the cross-linking of molecular chains, and improve the ability to resist external force stretching or compression.…”
Section: Introductionmentioning
confidence: 99%
“…32−34 Although controversial, the heterojunction of ZnO and ZnS (ZnO/ZnS) is known to enable the Z-scheme charge-transfer mechanism upon excitation, allowing much higher photocatalytic activity than each single-component catalyst. 33,35,36 However, owing to the lack of synthetic methods available to form the ZnO−ZnS heterostructure on UCNP, no previous study exists. 29 In this study, we demonstrated a two-step growth method of ZnO/ZnS NPs on NaYF4:Yb 3+ ,Tm 3+ (UCNP).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most UCNP-coupled photocatalysts are developed via costly and complicated synthesis with a selective range of light absorptions such as UV–NIR, and difficult postmodification of the photocatalyst component, which is often necessary to enhance the charge separation via the type II heterojunction or the Z-scheme mechanism . Previously, ZnO had responded to a broader range of photoexcitation energy and exhibited higher photocatalytic activity upon forming a heterojunction with ZnS. Although controversial, the heterojunction of ZnO and ZnS (ZnO/ZnS) is known to enable the Z-scheme charge-transfer mechanism upon excitation, allowing much higher photocatalytic activity than each single-component catalyst. ,, However, owing to the lack of synthetic methods available to form the ZnO–ZnS heterostructure on UCNP, no previous study exists …”
Section: Introductionmentioning
confidence: 99%